2012
DOI: 10.1021/mz3003775
|View full text |Cite
|
Sign up to set email alerts
|

Strain-Promoted Cross-Linking of PEG-Based Hydrogels via Copper-Free Cycloaddition

Abstract: The synthesis of a 4-dibenzocyclooctynol (DIBO) functionalized polyethylene glycol (PEG) and fabrication of hydrogels via strain-promoted, metal-free, azide-alkyne cycloaddition is reported. The resulting hydrogel materials provide a versatile alternative in which to encapsulate cells that are sensitive to photochemical or chemical crosslinking mechanisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
121
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(124 citation statements)
references
References 28 publications
2
121
0
Order By: Relevance
“…This seminal work has been adopted rapidly by other groups as a powerful and benign coupling strategy in polymer and material science [89,90]. Meanwhile, intensive studies dedicated to the development of cyclooctyne reagents or cyclooctyne analogs have generated more reactive activated reagents (Figure 7) by adding electron-withdrawing groups or increasing ring strain, the reaction rates of which are comparable to those of ligand-less CuAAC [21].…”
Section: Strain-promoted [3+2] Azide-alkyne Cycloadditionmentioning
confidence: 99%
“…This seminal work has been adopted rapidly by other groups as a powerful and benign coupling strategy in polymer and material science [89,90]. Meanwhile, intensive studies dedicated to the development of cyclooctyne reagents or cyclooctyne analogs have generated more reactive activated reagents (Figure 7) by adding electron-withdrawing groups or increasing ring strain, the reaction rates of which are comparable to those of ligand-less CuAAC [21].…”
Section: Strain-promoted [3+2] Azide-alkyne Cycloadditionmentioning
confidence: 99%
“…Multi-arm PEG was functionalized with dibenzocyclooctyne (DBCO), which undergoes biocompatible and biorthogonal strain promoted alkyne-azide cycloaddition (SPAAC) click chemistry [28,29] with a di-azide functionalized PEG (PEG-2-Az) crosslinker for gel formation. The UAA p-azido-l-phenylalanine (pAzF), which provides azide functionality, was site-specifically incorporated into a cyan fluorescent protein (CFP), a mCherry fluorescent protein (mCh), and mCh decorated with a thrombin cut-site (AzTMBmCh).…”
Section: Introductionmentioning
confidence: 99%
“…The broad applicability of these materials was demonstrated by successful cell culturing of a range of cells, such as fibroblasts, human mesenchymal stem cells, and bone marrow derived stromal cells. [30][31][32][33] When culturing cells on hydrogels, it is important to understand how they interact with their surroundings. It has been stated that cells are able to feel the substrate they are attached to and that they will respond based on these external mechanical signals.…”
Section: Introductionmentioning
confidence: 99%
“…[34,35] For example, it has been shown that the differentiation of mesenchymal stem cells is dependent on substrate stiffness. Culturing on soft gels (0.1-1 kPa) led to neurons, but myoblasts were formed on stiffer substrates (8)(9)(10)(11)(12)(13)(14)(15)(16)(17) and cells differentiated into osteoblasts on rigid matrices (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40). [36] Recent research indicates that these stem cells retain their phenotype on a non-fouling zwitterionic hydrogel, independent of stiffness.…”
Section: Introductionmentioning
confidence: 99%